A forgotten nasogastric feeding tube that refuses to get out. Issue 2 (17th January 2017) - Galanopoulos, Michail; Tsigaridas, Athanasios; Varytimiadis, Lazaros; Papaefthymiou, Apostolis; Kalampalikis, Lazaros; Ladias, Spyridon; Mantzaris, Gerassimos J.
Key Clinical Message: Nasogastric tubes (NGT) are extensively used and generally harmless, yet loop formation and malpositioning are often reported especially when using thin NGT for enteral feeding which placed blindly; therefore, diligent follow‐up of NGT is required with confirmation of right placement, changing it to PEG if long use of NGT needed. Abstract : Nasogastric tubes (NGT) are extensively used and generally harmless, yet loop formation and malpositioning are often reported especially when using thin NGT for enteral feeding which placed blindly; therefore, diligent follow‐up of NGT is required with confirmation of right placement, changing it to PEG if long use of NGT needed.